Economic evaluation of stepped care for the management of childhood anxiety disorders: Results from a randomised trial. (July 2019) - Chatterton, Mary Lou; Rapee, Ronald M; Catchpool, Max; Lyneham, Heidi J; Wuthrich, Viviana; Hudson, Jennifer L; Kangas, Maria; Mihalopoulos, Cathrine
Background: Stepped care has been promoted for the management of mental disorders; however, there is no empirical evidence to support the cost-effectiveness of this approach for the treatment of anxiety disorders in youth. Method: This economic evaluation was conducted within a randomised controlled trial comparing stepped care to a validated, manualised treatment in 281 young people, aged 7–17, with a diagnosed anxiety disorder. Intervention costs were determined from therapist records. Administrative data on medication and medical service use were used to determine additional health care costs during the study period. Parents also completed a resource use questionnaire to collect medications, services not captured in administrative data and parental lost productivity. Outcomes included participant-completed quality of life, Child Health Utility – nine-dimension and parent-completed Assessment of Quality of Life – eight-dimension to calculate quality-adjusted life years. Mean costs and quality-adjusted life years were compared between groups at 12-month follow-up. Results: Intervention delivery costs were significantly less for stepped care from the societal perspective (mean difference −$198, 95% confidence interval −$353 to −$19). Total combined costs were less for stepped care from both societal (−$1334, 95% confidence interval −$2386 to $510) and health sector (−$563, 95% confidence interval −$1353 to $643) perspectives but did not differ significantly from the manualised treatment. Youth and parental quality-adjusted life years were not significantly different between groups. Sensitivity analysis indicated that the results were robust. Conclusion: For youth with anxiety, this three-step model provided comparable outcomes and total health sector costs to a validated face-to-face programme. However, it was less costly to deliver from a societal perspective, making it an attractive option for some parents. Future economic evaluations comparing various models of stepped care to treatment as usual are recommended.